Photocatalytic oxidation of glucose in water to value-added chemicals by zinc oxide-supported cobalt thioporphyrazine. Issue 24 (14th November 2019) - Cheng, Ming; Zhang, Quanquan; Yang, Changjun; Zhang, Bingguang; Deng, Kejian
Abstract : Efficient photocatalytic oxidation of glucose into value-added chemicals was achieved by ZnO/CoPzS8 composite in water, the presence of CoPzS8 changed the glucose reaction pathway and glucaric acid was obtained in this photocatalytic system. Abstract : A new composite photocatalyst, ZnO/CoPzS8, was obtained by immobilizing cobalt tetra(2, 3-bis(butylthio)maleonitrile)porphyrazine (CoPzS8 ) onto the surface of home-prepared ZnO. The ZnO/CoPzS8 composite was well characterized by X-ray diffraction (XRD), UV-vis diffuse reflectance spectroscopy (DRS), X-ray photoelectron spectroscopy (XPS) and Raman spectroscopy. It turned out that CoPzS8 was successfully loaded onto the ZnO surface and there existed an interaction between ZnO and CoPzS8 . By using the ZnO/CoPzS8 composite photocatalyst, the photocatalytic oxidation of glucose to value-added chemicals in pure water was conducted under simulated sunlight irradiation without adding any acid or base. The ZnO/CoPzS8 composite exhibited a higher photocatalytic activity in comparison to pure ZnO and pure CoPzS8 owing to the synergistic effect between ZnO and CoPzS8 . Gluconic acid, arabinose, glycerol and formic acid were all observed as oxidation products when pure ZnO or ZnO/CoPzS8 composite was used. More importantly, glucaric acid was also obtained in the ZnO/CoPzS8 photocatalytic system, indicating that the presence of CoPzS8 changed the glucose reaction pathway. In addition, the active species generated in the photocatalytic process were further identified by electron spin resonance (ESR) technology and scavenger experiments. A possible photocatalytic conversion pathway of glucose has been proposed according to the experimental results.